BIAYA PRODUKSI DAN HARGA JUAL TERHADAP PROFITABILITAS UMKM SEKTOR KULINER SAJI DI KECAMATAN PADANG UTARA - Laynita Sari; Enjelita Adesti; Dewi Zulvia (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
This study aims to analyze the effect of production costs and selling prices on the profitability of Micro, Small, and Medium Enterprises (MSMEs) in the culinary sector in Padang Utara District. The method used in this research is a quantitative approach with multiple linear regression analysis. The sample in this study consisted of 92 MSME actors in the culinary sector in Padang Utara District, selected using the Yamane formula. The results of this study indicate that production costs have a positive and significant effect on profitability. Meanwhile, selling prices also have a positive and significant effect on profitability. These findings indicate that effective and efficient management of production costs, as well as appropriate pricing strategies, play an important role in increasing MSME profitability.